Efeito do carvacrol sobre biofilmes de Salmonella spp. em aço inoxidável - Uchida, Nancy Sayuri (2012)
The aim of this study was to evaluate the effect of carvacrol on Salmonella spp. biofilms on stainless steel surface. The effect of carvacrol on plank tonic cells was evaluated by determining minimum inhibitory concentration and minimal bactericidal concentration. The action of carvacrol on Salmonella spp. biofilms on stainless steel surface was evaluated on mature biofilm and on biofilm formation by enumerating the number of bacterial cells adhered and by scanning electron microscopy. A strong antimicrobial activity of carvacrol in plank tonic cells of Salmonella spp. was observed. The highest inhibitory activity of carvacrol was observed on biofilm formation at different sub inhibitory concentrations tested. The carvacrol reduced the number of bacterial cells adhered to stainless steel surface, which makes it a potential compound for Salmonella spp. control. Significance and Impact Study: Salmonella spp. infection is a public health problem in many countries. Due to difficulty of eliminating Salmonella spp. in biofilms, studies of alternative compounds for its control are essential.